2017
DOI: 10.5114/aoms.2017.65272
|View full text |Cite
|
Sign up to set email alerts
|

Tissue expression of β-catenin and E- and N-cadherins in chronic hepatitis C and hepatocellular carcinoma

Abstract: IntroductionThe role of Wnt/ β -catenin signaling pathway in HCV-associated hepatocellular carcinogenesis is still unknown.Material and methodsThis study aimed to perform quantitative analysis of immuno- and hybridocytochemical expression of β -catenin, E- and N-cadherins and HCV proteins (C, NS3, NS5A) in long-lasting (≥ 20 years) chronic hepatitis C (CH-C) (n = 54), hepatocellular carcinoma (HCC) (n = 61), and control liver samples (n = 8).ResultsTypical membranous expression of β -catenin in the control liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Hepatitis C virus (HCV) infection is a major health problem all over the world. It can cause chronic hepatitis and liver cirrhosis and represents the main risk factor of primary hepatocellular carcinoma [1]. It is estimated to chronically affect ~3% of the world's population (~170 million people), with more than one million new cases annually [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis C virus (HCV) infection is a major health problem all over the world. It can cause chronic hepatitis and liver cirrhosis and represents the main risk factor of primary hepatocellular carcinoma [1]. It is estimated to chronically affect ~3% of the world's population (~170 million people), with more than one million new cases annually [1].…”
Section: Introductionmentioning
confidence: 99%
“…It can cause chronic hepatitis and liver cirrhosis and represents the main risk factor of primary hepatocellular carcinoma [1]. It is estimated to chronically affect ~3% of the world's population (~170 million people), with more than one million new cases annually [1]. There is great variability in HCV prevalence rate from one country to another and even within the same country from one region to another [2].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of adhesive protein genes such as e-cadherin and n-cadherin was higher under the in uence of GO nano lm and nfGO + CELE, especially in HepG2 cells, but most important was a reduction in βcatenin expression in these cells [11,54,59]. Our results, like Mu et al, showed that cells increase the expression of E-cadherin on nfGO, moreover, in view of the fact that the weakening of tight connections (E-cadherin expression) and an increase in exible cell-cell contacts (N-cadherin expression) is characteristic of HCC [21].…”
Section: Discussionmentioning
confidence: 99%
“…Our results, like Mu et al, showed that cells increase the expression of E-cadherin on nfGO, moreover, in view of the fact that the weakening of tight connections (E-cadherin expression) and an increase in exible cell-cell contacts (N-cadherin expression) is characteristic of HCC [21]. Thus, the increase in expression of two types of intercellular junctions suggests that the experimental factors used (nfGO and CELE) did not increase the invasion of HepG2 cells [21,59,60]. These results are also con rmed by the observation of cell morphology, which re ects the cell-ECM and cell-cell relationship and also indicates material biocompatibility [32,61,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…HCV proteins affect in a double manner expression of E-cadherin, including modulation of the Wnt pathway and reduction of E-cadherin expression at the transcriptional level. Alterations in cellular locations of β-catenin and E-cadherin in chronic HCV and HCC pointed to structural disturbances in intercellular junctions in livers and presence of the transcriptionally inactive form of β-catenin [55,56] . Promoter hypermethylation of Wnt inhibitors was discovered in HCV-induced multistep hepatocarcinogenesis [57] , and the reduced expression of E-cadherin in long-lasting chronic HCV might represent an early indicator of the epithelial-mesenchymal transition [58,59] .…”
Section: Hcv Provoked Wnt Signalingmentioning
confidence: 99%